PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) PADA PEMBERIAN BERBAGAI JENIS MULSA - Fadel, Fadel; Yusuf, Ramal; Syakur, Abd. (AGROTEKBIS, 2017)
This research was conducted in Bulupountu Dusun Jaya, District Sigi Biromaru, Sigi in June to October 2015. This study was conducted to compare the effect of various mulch types (organic and inorganic) on the growth and yield of tomato (Lycopersicum esculentum Mill). This study uses a randomized block design consisted of five treatments, A0 = without mulch, A1= black plastic mulch, A2=silver plastic mulch, A3 = johar leaf mulch, A4 = rice straw mulch. Each treatment was repeated five times so that there are 25 experimental units. Mulching can increase growth and yield of tomato plants. Type silver plastic mulch provides the best growth and yield of tomato plants, especially on fruit weight parameters.Â Key Words: Growth, Mulch, tomato plants.